Rhodium(III)‐Catalyzed Regioselective Direct C4‐Alkylation and C2‐Annulation of Indoles: Straightforward Access to Indolopyridone. Issue 12 (26th March 2018) - Biswas, Aniruddha; Samanta, Rajarshi
Abstract : A straightforward Rh III ‐catalyzed strategy was developed for the site‐selective C4‐alkylation and C2‐annulation of indole by using electronically variable diazo esters. The transformation was accomplished with the assist of an oxime directing group at the C3 position of the indole core with wide scope and functional‐group tolerance. The method directly provided an indolopyridone core. The selectivity was triggered by the reactivity of the diazo coupling partner. Abstract : Rh III ‐catalyzed site selective C4‐alkylation and C2‐annulation of indole derivative has been developed by using variable diazo esters. Fine tuning of the reactivity of diazo esters leads to control in regioselectivity with wide scope and functional‐group tolerance. A straightforward approach has been established to furnish an indolopyridone scaffold.